2010
DOI: 10.1074/jbc.m109.098293
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Receptor Is Involved in Cell Surface Expression of A2B Receptor

Abstract: The A2A and A2B adenosine receptors (A2AR and A2BR) are implicated in many physiological processes. However, the mechanisms of their intracellular maturation and trafficking are poorly understood. In comparative studies of A2AR versus A2BR expression in transfected cells, we noticed that the levels of cell surface expression of A2BR were significantly lower than those of A2AR. A large portion of the A2BR was degraded by the proteasome. Studies of cell surface expression of A2BR chimeric molecules in transfecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 61 publications
6
48
1
Order By: Relevance
“…Although it is known that A 2A R expression increases in hypoxic/ischemic conditions (2), we considered that it would be pointless to attempt to highlight here a putative ischemia-induced adaptive increase in A 2A R expression during EST because the duration of the test is < 10 min in our patients, which is well below the time needed by the de novo synthesis and cell surface expression of A 2A R (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that A 2A R expression increases in hypoxic/ischemic conditions (2), we considered that it would be pointless to attempt to highlight here a putative ischemia-induced adaptive increase in A 2A R expression during EST because the duration of the test is < 10 min in our patients, which is well below the time needed by the de novo synthesis and cell surface expression of A 2A R (28).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless our studies do not unequivocally prove that A 2B AR reside within mitochondria; they may in fact only be loosely attached on the outside. Moriyama and Sitkovsky [29] recently showed that A 2B AR are poorly trafficked to the membrane in some cells leaving many receptors in the endoplasmic reticulum of the Golgi. However, the location of the receptors in our study is not consistent with a peri-nuclear Golgi locus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some of the pharmacological differences in A 2A receptor antagonists (that were tested for anti-parkinsonian effects in an animal model of Parkinson’s disease) may be correlated with differences in receptor heterodimerization (A 2A -D 2 versus A 2A –A 1 ) at postsynaptic and presynaptic sites 208,209 . Moreover, it was recently suggested that the presence of the A 2A receptor may be important for the proper targeting of A 2B receptors to cell surface membranes, through the formation of A 2A –A 2B receptor heterodimers 210 .…”
Section: Overview Of Adenosine Receptorsmentioning
confidence: 99%